2008
DOI: 10.1084/jem.20071555
|View full text |Cite
|
Sign up to set email alerts
|

Somatic diversification in the absence of antigen-driven responses is the hallmark of the IgM+IgD+CD27+ B cell repertoire in infants

Abstract: T cell–dependent immune responses develop soon after birth, whereas it takes 2 yr for humans to develop T cell–independent responses. We used this dissociation to analyze the repertoire diversification of IgM+IgD+CD27+ B cells (also known as “IgM memory” B cells), comparing these cells with switched B cells in children <2 yr of age, with the aim of determining whether these two subsets are developmentally related. We show that the repertoire of IgM+IgD+CD27+ B cells in the spleen and blood displays no s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
151
0
2

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 143 publications
(161 citation statements)
references
References 60 publications
(54 reference statements)
8
151
0
2
Order By: Relevance
“…This is not regularly seen in class-switched CD27-expressing B cells. In a recent study in infants, mutations in IgDϩ memory B cells were shown to increase from 60% to 83% within the first year of life (35). This corresponds well to the findings of the present study, in which 88% of the sequences in adults were identified as mutated, which is consistent with the notion that these cells undergo somatic mutations slowly with age.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This is not regularly seen in class-switched CD27-expressing B cells. In a recent study in infants, mutations in IgDϩ memory B cells were shown to increase from 60% to 83% within the first year of life (35). This corresponds well to the findings of the present study, in which 88% of the sequences in adults were identified as mutated, which is consistent with the notion that these cells undergo somatic mutations slowly with age.…”
Section: Discussionsupporting
confidence: 92%
“…Therefore, IgDϩ memory B cells are likely generated outside of GCs and are potentially subject to less stringent negative selection (39). The presence of these cells in infants younger than 2 years (35) confirmed that these cells generate at an early age but do not display signs of antigen-driven activation. The independence of GCs may render these cells particularly sensitive to rituximab-induced microenvironmental changes as discussed below.…”
Section: Discussionmentioning
confidence: 58%
“…During the last decade significant number of papers described various antibody disorders and their relationship to abnormalities in the distribution of B lymphocyte subpopulations. Although most authors refer to adult population, an increasing number of papers describes abnormalities in distribution of B cell subsets in pediatric patients with antibody deficiencies (2)(3)(4)(5). Interpretation of these results is difficult, as reliable reference values for pediatric population, in which distribution of most cell populations significantly vary with age, are currently not available.…”
mentioning
confidence: 99%
“…However, if the normal B cell counterparts should absolutely be searched, we should consider also the arguments that human marginal zone B cell population is a separate population that develops and www.intechopen.com diversifies Ig receptor outside T cell-dependent or -independent immune responses (Weill et al, 2009). In addition, considering the possibility of somatic diversification independent of antigen-driven responses and the existence of the subpopulation of circulating "memory" long-lived B cells harbouring a pre-diversified immunoglobulin repertoire in humans, then the concept of CLL cell origin may also radically differ from above hypotheses of two origin models (Weller et al, 2004;Weill & Reynaud, 2005;Weller et al, 2008). Alternatively, irrespectively to normal cellular counterparts, CLL cells may emerge from initially damaged cell in bone marrow which subsequently followed a development and immunoglobulin diversification according to the extend of its initial damage.…”
Section: Introductionmentioning
confidence: 99%